Trifluoroselenomethionine: A New Unnatural Amino Acid. (7th September 2016) - Block, Eric; Booker, Squire J.; Flores‐Penalba, Sonia; George, Graham N.; Gundala, Sivaji; Landgraf, Bradley J.; Liu, Jun; Lodge, Stephene N.; Pushie, M. Jake; Rozovsky, Sharon; Vattekkatte, Abith; Yaghi, Rama; et al.
Abstract: Trifluoroselenomethionine (TFSeM), a new unnatural amino acid, was synthesized in seven steps from N ‐( tert ‐butoxycarbonyl)‐l ‐aspartic acid tert ‐butyl ester. TFSeM shows enhanced methioninase‐induced cytotoxicity, relative to selenomethionine (SeM), toward HCT‐116 cells derived from human colon cancer. Mechanistic explanations for this enhanced activity are computationally and experimentally examined. Comparison of TFSeM and SeM by selenium EXAFS and DFT calculations showed them to be spectroscopically and structurally very similar. Nonetheless, when two different variants of the protein GB1 were expressed in an Escherichia coli methionine auxotroph cell line in the presence of TFSeM and methionine (Met) in a 9:1 molar ratio, it was found that, surprisingly, 85 % of the proteins contained SeM residues, even though no SeM had been added, thus implying loss of the trifluoromethyl group from TFSeM. The transformation of TFSeM into SeM is enzymatically catalyzed by E. coli extracts, but TFSeM is not a substrate of E. coli methionine adenosyltransferase. Abstract : Fluorinated amino acids : Trifluoroselenomethionine, a new unnatural amino acid, shows enhanced methioninase‐induced cytotoxicity, relative to selenomethionine, toward human colon cancer cells. Surprisingly, E. coli given 9:1 trifluoroselenomethionine/methionine mainly afford proteins containing selenomethionine units. The removal of the trifluoromethyl group in E. coli is enzymatically catalyzed.